Pre-service Teachers Perception of the Use of E-learning During Covid-19 Pandemic in Colleges of Education in North-West, Nigeria - Abdullahi Abubakar Ismaila; Umar Bello; Isiaka Amosa Gambari (Indonesian Educational Research Journal, 2024)
This study of pre-service teachers’ perception of the use of e-learning during the Covid-19 pandemic in colleges of education in the North-west, Nigeria, was guided by two objectives; to find out the availability of e-learning tools in colleges of education in North-west, Nigeria during Covid-19, to investigate the perceived usefulness of e-learning by the pre-service teachers in colleges of education in North-west, Nigeria during Covid-19 and two research questions; are e-learning tools available for teaching and learning in colleges of education in North-west, Nigeria during Covid-19? How do pre-service teachers perceive the usefulness of e-learning in colleges of education? The researchers used mixed methods (quantitative and qualitative) for data collection.  A Multistage (called clustering) sampling technique was employed to select the sample from the colleges of education in North-west, Nigeria. The total population of the study is 113,030. The total sample that was chosen is 372 for quantitative and 23 for qualitative. The instruments used for data collection were adapted (questionnaires were used for quantitative, while data-blank was used for qualitative). The frequency and percentage were employed to analyze the respondents’ demographic information. The summary of the major findings points out that, there are no adequate e-learning resources in colleges of education in North-west, Nigeria that will enable them to use e-learning during Covid-19, and the pre-service teachers in colleges of education in North-west, Nigeria didn’t use to e-learn during Covid-19. The study affirmed that e-learning can be used as an instructional tool in colleges of education in North-west, Nigeria.